EVALUASI SELEKSI PERANGKAT DESA KEBUMEN, KECAMATAN BANYUBIRU, KABUPATEN SEMARANG TAHUN 2017 - Endry Chrisnurlenawati; Kushandajani . (Journal of Politic and Government Studies, 2019)
Kebumen Village is one of the villages that participated in the selection of village officials in 2017. Interesting incident had occurred in the selection of Kebumen village equipment. The results of the selection tests for the Kebumen village equipment state that the first rank of each position formation offered by a couple is accidentally achieved. This research aims to evaluate the selection process of Kebumen village according to “Peraturan Bupati Nomor 38 Tahun 2016 tentang Tata Cara Pengangkatan dan Pemberhentian Perangkat Desa“. This study uses a qualitative descriptive research method. Sources of data are taken from primary data based on information from sources and secondary data obtained from other sources and data. The results of this study found that the implementation of the Kebumen Village Toolkit, which had been implemented for the first time, had run smoothly. However, there are still some violations of the selection procedures for the Kebumen Village. In addition, there is no turmoil from the community so that the peace of society is more maintained because the results of the selection are objective that come from selection tests.